2015
DOI: 10.1105/tpc.114.135160
|View full text |Cite
|
Sign up to set email alerts
|

VIH2 Regulates the Synthesis of Inositol Pyrophosphate InsP8 and Jasmonate-Dependent Defenses in Arabidopsis

Abstract: ORCID IDs: 0000-0002-7823-5489 (D.L.); 0000-0002-4512-9508 (P.J.); 0000-0002-1025-9484 (H.J.J.); 0000-0001-9022-4515 (G.S.)Diphosphorylated inositol polyphosphates, also referred to as inositol pyrophosphates, are important signaling molecules that regulate critical cellular activities in many eukaryotic organisms, such as membrane trafficking, telomere maintenance, ribosome biogenesis, and apoptosis. In mammals and fungi, two distinct classes of inositol phosphate kinases mediate biosynthesis of inositol pyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
327
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 157 publications
(349 citation statements)
references
References 82 publications
(103 reference statements)
11
327
0
Order By: Relevance
“…Indeed, the inositol pyrophosphate InsP 5 has been shown to potentiate the assembly of the COI1-JAZ complex in vitro (Sheard et al, 2010). A recent report showed that VIH2, a PPIP5K regulating the biosynthesis of InsP8, plays an important role in JA signaling and suggests that InsP8 is a critical cofactor in COI1-JAZ complex formation (Laha et al, 2015). This model may explain the inability of COR to open stomata in the rin4 mutant, which may be defective in the generation of such a cofactor.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the inositol pyrophosphate InsP 5 has been shown to potentiate the assembly of the COI1-JAZ complex in vitro (Sheard et al, 2010). A recent report showed that VIH2, a PPIP5K regulating the biosynthesis of InsP8, plays an important role in JA signaling and suggests that InsP8 is a critical cofactor in COI1-JAZ complex formation (Laha et al, 2015). This model may explain the inability of COR to open stomata in the rin4 mutant, which may be defective in the generation of such a cofactor.…”
Section: Discussionmentioning
confidence: 99%
“…position 5 of the inositol ring, an activity which is distinct from the activity of VIP proteins that act on the 1/3 positions (Lin et al, 2009) ( Figure 2C). The two VIP paralogs of Arabidopsis (AtVIP1 and AtVIP2; also called AtVIH1 and AtVIH2) can complement a yeast vip1 deletion (Desai et al, 2014) and are required for jasmonate defense signaling (Laha et al, 2015). A QTL for vitamin E levels also mapped to one of the two Arabidopsis VIP genes (At3g01310) (Gilliland et al, 2006), though a connection between InsPs and vitamin E has not been directly established.…”
Section: Chlamydomonas Vip1 Provides An Entrée Into Inositol Polyphosmentioning
confidence: 99%
“…The predicted Chlamydomonas VIP1 protein (CrVIP1) showed high-scoring BLASTP similarity to a conserved family of eukaryotic diphosphoinositol pentakisphosphate kinases of the VIP family (Mulugu et al, 2007;Desai et al, 2014;Laha et al, 2015). VIP proteins contain two conserved domains, an ATP_GRASP domain (pfam 13535) that is predicted to have inositol diphosphate kinase activity (Mulugu et al, 2007;Fridy et al, 2007;Lin et al, 2009;Pöhlmann et al, 2014) followed by a histidine phosphatase domain (pfam 00328) that in CrVIP1 is interrupted with nonconserved sequences (Figure 2A).…”
Section: Vip1 Encodes a Predicted Diphosphoinositol Pentakisphosphatementioning
confidence: 99%
See 1 more Smart Citation
“…The IP6Ks (InsP 6 kinase) are able to pyrophosphorylate position 5 of the inositol ring, generating 5PP-InsP 5 (diphosphoinositol pentakisphosphate, InsP 7 ) from InsP 6 or 5PP-InsP 4 from Ins(1,3,4,5,6)P 5 [25,[38][39][40][41][42][43]. Alternatively, PPIP5K (VIP1 in yeast) enzymes can pyrophosphorylate position 1, generating the 1PP-InsP 5 isomer of InsP 7 from InsP 6 in vitro [44][45][46][47], and InsP 8 ([PP] 2 -InsP 4 ; bisdiphosphoinositol-tetrakisphosphate) from 5PP-InsP 5 in vivo [48,49].…”
Section: Phosphoinositides and Inositol Phosphatesmentioning
confidence: 99%